Cromatografia líquida bidimensional aplicada a senosídeos e na determinação simultânea de diclofenaco sódico, paracetamol e cafeína - Favarin, Fábio Henrique Pinheiro (2012)
In this study are proposed analytical methods involving the two-dimensional liquid chromatography for drug analysis. The twodimensional liquid chromatography (LC × LC) provides an increase in peak separation ability as compared with the technique dimensional. With its more powerful separation occurs reducing co-elutions, allowing better quantification. The orthogonal separation based on different separation mechanisms may improve the selectivity and facilitate analysis of compounds in complex samples. One of the principles characterizing 2D-LC technique is to use orthogonal methods to each other, thus peaks are eluted in the sequence A, B, C in the first column are eluted into another sequence in the second column that is orthogonal to the first . Selectivity is the ability of the chromatographic system of discriminating different analytes and is determined as the ratio of the retention factor of two analytes, or the ratio of the retention times. In the method 2D-LC, fractions should be collected after passing through a first column and reinjected into another column, thus, a chromatographic run 10 minutes at a flow rate of 1 ml / min, collecting fractions of 1 mL, 10 represents new injections. These fractions reinjected into a second column chromatograms new generation 10, which when joined together give rise to a chromatographic surface. Two-dimensional chromatograms are important to evaluate overlapping chromatographic peaks not able to be viewed on a conventional chromatographic analysis. The samples used for both tests were quantified by calculation of content and it was found that methods are needed, reproductive and fractions collected when compared with quantified method had good initial recovery. Methods have been developed for determination of senosides (series of anthraquinone derivatives with laxative effect), and dimeric occurring glycosides abundant in plants of the genus Senna and methods for determining the content of diclofenac sodium, paracetamol and caffeine. The samples were subjected to stress conditions to evaluate the appearance of new substances, characterized as impurities and / or degradation products. Comparing the results between one-dimensional and two-dimensional technique, note the significant increase in the selectivity of the peaks, and the resolution between them. In a dimensional analysis often requires a very long running time for complete separation of the peaks. Developing two-dimensional methods can significantly reduce the running time on a first column, causing the overlapping peaks are separated in a second stationary phase, gaining in selectivity.